The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.11648/j.ejcbs.20180404.11
|View full text |Cite
|
Sign up to set email alerts
|

Patient Delay and Associated Factors Among Pulmonary Tuberculosis Patients at Hadiya Zone Public Health Facilities in South Ethiopia, 2017

Abstract: Early diagnosis and immediate initiation of treatment are essential for an effective TB control program. Delay in treatment is significant to both disease prognoses at the individual level and within the community. Patient delay and associated factors were assessed among pulmonary tuberculosis patients who are on treatment for the first two months at Hadiya zone public health facilities, south Ethiopia, 2017. Facility based cross sectional study triangulated by Qualitative study was employed on 340 Pulmonary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Ethiopia is one of the high TB, TB/HIV and MDR-TB burden countries [14] with an estimated prevalence of 108 per 100,000 population in smear-positive drug susceptible TB individuals [15]. In Ethiopia there are several studies that reported health facility related treatment initiation delay among TB patients [16][17][18][19][20][21]. However, few studies are conducted on the health seeking behavior from health facilities among presumptive TB patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia is one of the high TB, TB/HIV and MDR-TB burden countries [14] with an estimated prevalence of 108 per 100,000 population in smear-positive drug susceptible TB individuals [15]. In Ethiopia there are several studies that reported health facility related treatment initiation delay among TB patients [16][17][18][19][20][21]. However, few studies are conducted on the health seeking behavior from health facilities among presumptive TB patients.…”
Section: Introductionmentioning
confidence: 99%